Defending Against Source Routing Attacks and Packet Forwarding in Ad-Hoc Networks - Kolla, Sriharibabu (International Journal of Computer Sciences and Engineering, 2014)
A wireless Ad-hoc network is the collection of wireless nodes that can co-operate by forwarding packets for each other to allow nodes to communicate directly. The prominence of the place of wireless ad-hoc networking is become more crucial to everyday functioning of people. This is due to obvious advantages of the wireless networks with ubiquity access and minimal hardware requirements in networks. The ad-hoc nature of sensor network means no structure can be statically defined. The network topology is always subject to change due to node failure, addition or mobility. Since nodes may fail or be replaced the network must support self-configuration. Routing and data forwarding is a crucial service for enabling communication in ad-hoc networks. Unfortunately, current routing protocols suffer from many security vulnerabilities. In this paper prior security work in this area focused primarily on source routing attacks. Low power wireless networks are an existing research direction in routing and packet forwarding.